PTH-329 Expression of pigment epithelium-derived factor in colorectal cancer. (22nd June 2015) - Harries, RL; Cai, J; Li, J; Owen, S; Harding, K; Torkington, J; Jiang, W
Abstract : Introduction: Pigment epithelium-derived factor (PEDF) is a 50kDa, secreted glycoprotein that has been identified as a member of the serpin gene family and has been shown to exhibit neurotrophic, neuroprotective, anti-angiogenic and anti-tumourigenic effects. The aims of our study were to determine the expression profile of PEDF in a range of colorectal cell lines and its association with clinical and pathological data. Method: Six human cell lines (RKO and HT115 are colonic adenocarcinoma, HRT-18 is rectal adenocarcinoma, COLO-201 is metastatic adenocarcinoma (originating from ascites), LS174T is a mucinous adenocarcinoma, and CCD-33C0 is a normal colorectal fibroblast cell line) were analysed using polymerase chain reaction (PCR) and quantitative transcript analysis (qPCR). Primary colorectal cancer tissue was collected at operation and analysed using qPCR. Results: PEDF transcript was positive in RKO, HRT-18, LS174T and CCD-33C0 cell lines but negative in HT115 and COLO-201. On qPCR, PEDF expression was highly positive in CCD-33C0. PEDF expression was significantly higher in tissue from mucinous tumours compared to adenocarcinoma (p = 0.0421). PEDF expression was lower in colorectal tissue from palliative resections compared to radical resections, with a trend towards significance (p = 0.097). Conclusion: PEDF expression was higher in the normal colorectal cell line when compared to colorectal cancer cell lines. There was a trend towards decreased expression in colorectal cancer tissue from palliative resections suggesting a possible tumour suppressor role and may indicate a potential role in primary tumour growth. Further work is proposed to investigate the effect of PEDF expression on cell function. Disclosure of interest: None Declared.